Peningkatan Keterampilan Menulis Narasi Budaya Lokal Menggunakan Metode Inquiry Mahasiswa Semester VI Prodi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Alauddin Makassar - Syamhari, Syamhari; Nasrum, Nasrum (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the use of the Inquiry Method in learning the skills of writing local cultural narratives for Semester VI Students of the Islamic Civilization History Study Program. The problem in this study is: How is the implementation of learning the skills of writing local cultural narratives using the inquiry method for semester VI students of the Islamic Civilization History Department, Faculty of Adab and Humanities, UIN Alauddin Makassar? The purpose of this study is to describe the improvement of local cultural narrative writing skills using the inquiry method for semester VI students of the Islamic Civilization History Department, Faculty of Adab and Humanities, UIN Alauddin Makassar. The results of this study are that the use of the inquiry method can improve the skills of semester VI students of the Islamic Civilization History Study Program, Faculty of Adab and Humanities, UIN Alauddin Makassar in writing local cultural narratives as described below: The results of the implementation of learning using the inquiry method obtained in the implementation of this learning are: in cycle I, it is still relatively low. This is evidenced by the percentage that gets the very good category on each test component such as: the very good category of the five test components is only 23 people overall or 12 percent who get the very good category. There are 43 people or 23 percent of the total number of test components who get the good category, 44 people or 23 percent who get the moderate category. Likewise, those who get the less category are 44 people or 23 percent, while those who get the very less category are 19 percent.